Influence of polymorphism of the MUC7 gene on oral hygiene, gingival status and dental plaque formation - Szmidt, Monika; Pol, Justyna; Buczkowska-Radlińska, Jadwiga (Journal of Stomatology, 2015)
Aim of the study. To analyze polymorphism of the MUC7 gene and its connection with dental plaque accumulation (24h Plaque Formation Rate Index), dental hygiene as described by API and gingival status (GBI and SBI). Material and methods. A total of 47 volunteers from among students of the second year of the Faculty of Dentistry participated in the study. Students were aged between 20 and 22 years. The procedure was performed under standard conditions in the dental chair with adequate light, by means of a mirror and a probe. The status of dental hygiene was determined with API. The condition of periodontium was determined using modified SBI and GBI. In all patients the dentist carried out professional teeth cleaning with “clean polish” paste and a brush, using slow handpiece. After this treatment all volunteers were asked to abstain from performing any form of oral hygiene practices for a period of 24 hours. Dental plaque accumulation was assessed by inspecting the presence of dental plaque using a dental probe. Quantification of dental plaque accumulation was carried out after 24h using PFRI – Plaque Formation Rate Index, modified for needs of this study. Genetic research was performed to isolate DNA, which was obtained by means of a Sherlock AX universal set (A&A BIOTECHNOLOGY). DNA identification of polymorphism of MUC 7 gene was performed using PCR – RLFP method. Results. Patients with MUC7*5/*6 genotype were statistically six times more susceptible to accumulate dental plaque when the PFRI was over 14. There was a significant correlation between PFRI and API. There was no significant difference between either PFRI or SBI, GBI. A statistically important correlation between the MUC7 gene, API and PFRI was revealed. Significantly higher value of GBI was correlated with PFRI, when the mean value of PFRI was over 15. Conclusions. This study showed that genetic polymorphism of the MUC7 gene is present in the examined group. A statistically significant correlation between MUC7 gene and the PFRI index was obtained. Higher API values corresponded with more rapid accumulation of dental plaque. The study showed no correlation between polymorphism of the MUC7 gene and API, SBI and GBI indices.